PERAN MEDIA SOSIAL TERHADAP PERILAKU KONSUMTIF KAUM REMAJA DI DESA TEGAL KERTHA, KECAMATAN DENPASAR BARAT, KOTA DENPASAR - Wisnu Hidayat, Tri Bagoes; Punia, I Nengah; Kebayantini, Ni Luh Nyoman (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT This thesis discusses about presence of social media in Indonesia society, has transformed teenagers behavior. The use of social media by teenagers today already in the stage where the media and the internet seemed to be a necessity that must fulfilled. So, in the end social media is developing not only as a social medium, but online trading media (e-commerce).This research uses theory simulation of Jean Baudrillard, applies discriptive method with data qualitative where the source of data obtained from in-depth interview with the informant that is adolescents who use social media as a tool to meet the consumptive needs. Based on the result of this research, consumptive behavior poses a negative and positive impact for teenagers. Keywords : Social media, Teenagers, Consumtive Behavior